2016
DOI: 10.9734/ibrr/2016/27534
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Rh (Rhesus) D Blood Group, Risk Factors and Burden of Rh D Alloimmunisation among Female Secondary School Students in Ikorodu, Lagos, Nigeria

Abstract: Background: Rh (Rhesus) blood group antigen especially D antigen plays a pivotal role in provision of safe blood and safe pregnancy. Antigen mismatch between blood donor and recipient or pregnant woman and the foetus sets the stage for immunohaematological complication such as haemolytic transfusion reaction and haemolytic disease of the foetus and newborn. Individual knowledge of the Rh blood group status among females of reproductive age group is a contributory measure for effective control and prevention of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 20 publications
1
6
1
Order By: Relevance
“…Several cross-sectional studies have been conducted to assess population awareness of Rh alloimmunization [14][15][16][17]. A Nigerian study, which enrolled 140 pregnant women attending ANC clinics, concluded that there was knowledge about Rh alloimmunization but poor awareness about the complications [17], which coincides with our results regarding awareness about complications but not about the Rh alloimmunization.…”
Section: Interpretation and Comparison With Other Literaturesupporting
confidence: 86%
See 3 more Smart Citations
“…Several cross-sectional studies have been conducted to assess population awareness of Rh alloimmunization [14][15][16][17]. A Nigerian study, which enrolled 140 pregnant women attending ANC clinics, concluded that there was knowledge about Rh alloimmunization but poor awareness about the complications [17], which coincides with our results regarding awareness about complications but not about the Rh alloimmunization.…”
Section: Interpretation and Comparison With Other Literaturesupporting
confidence: 86%
“…The questionnaire was designed based on previous similar articles and a literature search [12][13][14][15] using Google Forms, questionnaire link: https://docs.google.com/forms/d/e/1FAIpQLScYo7wnVBibbozXbill3sPGhhuSqxgIUl5UCPzqV8o Buc9iDA/viewform?usp=sharing). Before distributing the questionnaires, a pilot study was conducted involving 33 pregnant women, and its validity was checked by qualified specialists.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study carried out in Nigeria by Ogbenna et al provided that among 927 female secondary school students a very low proportion 13.2% were having knowledge about their own Rh blood group. (19). A study conducted in Ethiopia by Diriba et al (20) showed similar kind of result of low awareness regarding RH blood group.…”
Section: Discussionmentioning
confidence: 76%